Population assessment of health system performance in 16 countries - Kruk, Margaret (2024)
Objective To demonstrate how the new internationally comparable instrument, the People’s Voice Survey, can be used to contribute the perspective of the population in assessing health system performance in countries of all levels of income. Methods We surveyed representative samples of populations in 16 low-, middle- and high-income countries on health-care utilization, experience and confidence during 2022–2023. We summarized and visualized data corresponding to the key domains of the World Health Organization universal health coverage framework for health system performance assessment. We examined correlation with per capita health spending by calculating Pearson coefficients, and within-country income-based inequities using the slope index of inequality. Findings In the domain of care effectiveness, we found major gaps in health screenings and endorsement of public primary care. Only one in three respondents reported very good user experience during health visits, with lower proportions in low-income countries. Access to health care was rated highest of all domains; however, only half of the populations felt secure that they could access and afford high-quality care if they became ill. Populations rated the quality of private health systems higher than that of public health systems in most countries. Only half of respondents felt involved in decision-making (less in high-income countries). Within countries, we found statistically significant pro-rich inequalities across many indicators. Conclusion Populations can provide vital information about the real-world function of health systems, complementing other system performance metrics. Population-wide surveys such as the People’s Voice Survey should become part of regular health system performance assessments.